A framework for application of the landscape approach to forest conservation and restoration in Sierra Leone - Bakarr, Mohamed I.; Abu-Bakarr, Ibrahim (Frontiers in Forests and Global Change, 2022)
Sierra Leone has made some progress in creating protected areas for wildlife and biodiversity conservation. Yet deforestation and habitat loss remain pervasive, driven largely by unregulated exploitation and poor land use practices. With over 50% of the country (∼36,000 km2) having climate that is favorable for tropical forest vegetation, there is considerable opportunity to advance the landscape approach for forest conservation. We propose a framework to address this need for the globally threatened Upper Guinea rainforest, which has its westernmost extent in Sierra Leone. The framework considers forest and tree cover in the following categories: old growth, disturbed old growth, secondary growth, and managed. We discuss how this typology can foster application of the landscape approach to forest conservation and restoration, including policy options to enhance protection of forests, increase tree cover in production systems, and incentivize innovative land use practices by local communities.